자연사 특별기획전의 차별화된 전시기획 및 연출전략 연구 - 국립부산과학관 특별기획전 ‘다이노소어展’을 중심으로 - 김도연; Do-yeon Kim; 김철기; Cheol-ki Kim (한국디자인포럼, 2022)
연구배경 ‘공룡’은 표본 및 움직이는 모형 전시물 중심의 대표적인 자연사 전시 주제이다. 과학 사료 측면에서 희소성이 높고 대중에게 흥미로운 주제인 만큼 국내 다수의 과학관과 자연사박물관에서 전시되고 있다. 공룡전시를 특별기획전으로 개최하여 관람객의 관심을 유발하기 위해서는 기존 자연사 전시와는 차별화된 기획과 연출전략이 요구된다. 연구방법 본 연구는 공룡이라는 전시주제와 특별기획전이라는 전시 형태에 초점을 두고, 이론적 고찰을 통해 전시주제(공룡) 및 자연사 전시의 특성, 자연사 전시의 주요전시 매체와 표현방법 및 유형, 자연사 전시에서의 최적화 연출요소와 효과를 살펴보았다. 국내 공룡展의 현황과 특성을 분석하여 차별화 요소를 도출하고 연출 전략을 수립하였다. 이를 반영하여 실제 개최될 공룡展을 기획하였다. 연구결과 연구의 결과물로 총 14가지의 최적화 연출전략을 5가지(표본·설명 자료, 공간구조, 체험·특수요소)로 구분하여 반영한 국립부산과학관 특별기획전‘다이노소어展’의 기획안을 최종 제시하였다. 결론 특별기획전은 콘텐츠와 스토리, 구성을 어떻게 기획하느냐에 따라 동일 주제의 전시도 관람객에게 다르게 전달될 수 있다. 본 연구는 기존 상설전시관의 자연사 전시와 차별화된 전시 기획(안)을 도출하기 위한 연구 과정을 선보였으며, 이를 통해 특별기획전 기획 실무에서의 기초 자료를 마련하고자 한다. Background The‘Dinosaur’ is one of the main subjects in cemented specimen exhibition, mechanical model exhibition and natural history exhibition. As the dinosaur is a scientifically rare and publicly popular subject, it is displayed in many domestic science museums and natural history museums. Thus, a differentiated exhibition planning and strategy of direction is required to engage the audience of the dinosaur exhibition. Methods This study focused on the exhibition theme of dinosaurs and the exhibition form of special exhibitions and examined the characteristics of exhibition topics (dinosaurs) and natural history exhibitions, main exhibition media and expression methods, types, and optimization production factors and effects in natural history exhibitions. Differentiations and directing strategies were derived by analyzing the current status and characteristics of the domestic dinosaur exhibitions. Reflecting on this, the dinosaur exhibition was planned Result This study presents a plan for the Busan Science Museum's Special Planning Exhibition ‘Dinosaur’, which divided 14 optimization direction strategies into five direction strategies: sample data, explanatory data, spatial structure, experience, and special factors. Conclusion Depending on how the content, story, and composition of the special exhibition are planned, exhibitions of the same theme can be delivered differently to visitors. This study derived a differentiated exhibition plan from the existing permanent exhibition hall's natural history exhibition, and through this, it aims to prepare the basic data for the special exhibition planning practice.